ANALISIS RISIKO TEKNOLOGI INFORMASI MENGGUNAKAN ISO 31000 STUDI KASUS: LAYANAN EKSPEDISI XYZ: ANALISIS RISIKO TEKNOLOGI INFORMASI MENGGUNAKAN ISO 31000 STUDI KASUS: LAYANAN EKSPEDISI XYZ - Anindhita Ari Putri; Deva Istifadhah Irnanda (Jurnal Teknologi dan Terapan Bisnis, 2023)
This article introduces a method for measuring the level of risk in information technology that is appropriate for dealing with risk. XYZ Expedition is a shipping service company in the form of documents and packaging. XYZ Expedition is a new company that also uses IT when providing services, they provide the advantage of taking goods. If the customer wants to send goods, no need to go to the XYZ Expedition office, just contact via android and iOS based applications or via their official hotline. Information technology supports the company's business operations. In this way the risk of information technology can occur at any time. Therefore, an information technology risk analysis will be carried out using ISO 31000. This method will be used to seek the results of measuring risk and solving risk problems and risk management to run smoothly. The risk priority of each possible risk has been determined or identified. Thus, the results of this risk analysis can be used to help minimize risks that are handled appropriately.